Towards population-scale long-read sequencing. - De Coster, Wouter; Weissensteiner, Matthias H; Sedlazeck, Fritz J (Nat Rev Genet, 2021)
Long-read sequencing technologies have now reached a level of accuracy and yield that allows their application to variant detection at a scale of tens to thousands of samples. Concomitant with the development of new computational tools, the first population-scale studies involving long-read sequencing have emerged over the past 2 years and, given the continuous advancement of the field, many more are likely to follow. In this Review, we survey recent developments in population-scale long-read sequencing, highlight potential challenges of a scaled-up approach and provide guidance regarding experimental design. We provide an overview of current long-read sequencing platforms, variant calling methodologies and approaches for de novo assemblies and reference-based mapping approaches. Furthermore, we summarize strategies for variant validation, genotyping and predicting functional impact and emphasize challenges remaining in achieving long-read sequencing at a population scale.

Discovery and population genomics of structural variation in a songbird genus. - Weissensteiner, Matthias H; Bunikis, Ignas; Catalán, Ana; Francoijs, Kees-Jan; Knief, Ulrich; Heim, Wieland; Peona, Valentina; Pophaly, Saurabh D; Sedlazeck, Fritz J; Suh, Alexander; Warmuth, Vera M; Wolf, Jochen B W (Nat Commun, 2020)
Structural variation (SV) constitutes an important type of genetic mutations providing the raw material for evolution. Here, we uncover the genome-wide spectrum of intra- and interspecific SV segregating in natural populations of seven songbird species in the genus Corvus. Combining short-read (N = 127) and long-read re-sequencing (N = 31), as well as optical mapping (N = 16), we apply both assembly- and read mapping approaches to detect SV and characterize a total of 220,452 insertions, deletions and inversions. We exploit sampling across wide phylogenetic timescales to validate SV genotypes and assess the contribution of SV to evolutionary processes in an avian model of incipient speciation. We reveal an evolutionary young (~530,000 years) cis-acting 2.25-kb LTR retrotransposon insertion reducing expression of the NDP gene with consequences for premating isolation. Our results attest to the wealth and evolutionary significance of SV segregating in natural populations and highlight the need for reliable SV genotyping.
Keywords: Animals; Chromosome Inversion; Gene Deletion; Genetic Variation; Genetics, Population; Genome; Genomic Structural Variation; Genotype; Phylogeny; Polymorphism, Single Nucleotide; Retroelements; Sequence Analysis, DNA; Songbirds